Fungating Breast Cancer: Experience in Low and Middle Income Country - Bichoo, Raouef Ahmed (Indian J Surg Oncol, 2020)
Fungating breast cancer (FBC) is a rare entity in developed nations. But this occurrence is not uncommon in our country. The aim of this study was to review clinico-pathologic profile and outcomes of FBC in a developing country. This retrospective study consisted of patients with FBC managed at our institute (Jan 2005–Dec 2015). Clinico-pathologic profile, management details, and outcomes were analyzed. The Kaplan-Meier method was used to determine overall survival (OS). Log-rank test was performed to compare survival in various subgroups. Seventy-nine patients were detected to have FBC constituting 3.3% of all breast cancers and 24.8% of those having T4b lesions. Mean age of the patients was 55 + 11 years. Ninety-six percent were women and 67% belonged to rural areas. A total of 75% women were postmenopausal. Mean duration of lump was 16 + 11 months. The mean tumor size was 8+ 2 cm. Eighty-seven percent had axillary lymph node involvement and 42% distant metastases. Fifty-eight percent (n = 46) patients had stage III and 42% (n = 33) stage had IV tumors. Hormone receptor (HR) positivity was noted in 44% (n = 35) and HER2/neu overexpression in 39% (n = 31) tumors, whereas 32% (n = 25) were triple negative. Overall, 95% (n = 75) of patients received chemotherapy, 91% (n = 72) patients underwent mastectomy, and 76% (n = 60) loco-regional radiotherapy. Median duration of follow-up was 40 (2–93) months. Median survival was 36 months, and 5-year OS was 40%. Except for stage (53% vs 22%, p = 0.005), no other factor influenced OS. Multimodality therapy in FBS results in good symptom palliation and comparable survival to stage III and IV patients without fungating tumors.